2018
DOI: 10.3390/cosmetics5020030
|View full text |Cite
|
Sign up to set email alerts
|

A Critical View of Different Botanical, Molecular, and Chemical Techniques Used in Authentication of Plant Materials for Cosmetic Applications

Abstract: A number of approaches can be implemented to ensure plant-based material authentication for cosmetic applications. Doing this requires knowledge and data dealing with botany, molecular biology, and analytical chemistry, the main techniques of which are described here. A comprehensive and critical view of the methods is provided with comments as well as examples of their application domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…These processes are an indispensable step to promote the progression in drug discovery and development using phytochemical compounds. Asian region is well-known as one of the greatest hotspot of plant biodiversity including medicinal species, especially Japan, China, Thailand and related areas in tropical and sub-tropical regions [ 6 , 54 , 67 , 74 , 104 , 105 ]. However, a comprehensive profiling of many medicinal plants and functional evaluation of their chemical compound has not been completely conducted.…”
Section: Profiling Work and The Survey Of Flavonoids And Other Phmentioning
confidence: 99%
“…These processes are an indispensable step to promote the progression in drug discovery and development using phytochemical compounds. Asian region is well-known as one of the greatest hotspot of plant biodiversity including medicinal species, especially Japan, China, Thailand and related areas in tropical and sub-tropical regions [ 6 , 54 , 67 , 74 , 104 , 105 ]. However, a comprehensive profiling of many medicinal plants and functional evaluation of their chemical compound has not been completely conducted.…”
Section: Profiling Work and The Survey Of Flavonoids And Other Phmentioning
confidence: 99%
“…In vitro culture techniques provide consistent production schemes for metabolites that are free from environmental limitations and ensure increased biomass and a high concentration of compounds compared to natural production systems [ 13 ]. In addition, in the case of basil varieties or cultivars which can be differentiated on the basis of color, aromatic composition and growth habitat, sometimes harvested from nature, thus complicating its botanical identity, the in vitro system presents a major advantage for the certification of plant authentication [ 4 , 14 ]. Various reports are available in the literature on the in vitro production of bioactive metabolites from the callus culture of medicinally important plants.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there are currently no report on the geographic effect on flavonoid compounds of the kudzu plant. However, some species that are widely distributed, such as flax [6] and other economic plants were studied, and the results indicated that cultivar type, geographic site, and cultivation time influence phytochemical compounds and biological activities.…”
Section: Next Challenging Perspectives and Research Directionsmentioning
confidence: 99%
“…A large number of its flavonoid phytochemical compounds have been reported [1][2][3][4]. In this era of modern research and innovation, the cosmetic sector is seeking for alternative choices of plant extracts and/or natural products containing potential bioactive compounds for cosmetic product development [5,6]. Flavonoids are the popular choice of those potential bioactive phytochems for cosmetic applications.…”
Section: Introductionmentioning
confidence: 99%